German Food Security in Times of Crisis - Мaria V. Khorolskaya (Современная Европа)
The article deals with the German food security during the conflict in Ukraine. The study analyses the German food system resilience and the Ukrainian crisis impact on food security. The author aims to solve several scientific problems as well. The article examines the German understanding of food security and how the national concept corresponds to the approaches of international organisations. The author analyses the level of self-sufficiency in basic food products in Germany and the impact of the Ukrainian conflict on various imported food products. She examines official documents of the UN FAO, the government of Germany, and the Federal Ministry of Agriculture and Food to identify the conception of food security in Germany. The researcher scrutinises statistic data provided by the Federal Ministry of Food and Agriculture, the Federal Office for Food and Agriculture, the Federal Statistical Office and concludes about the level of German self-sufficiency in food. The interpretation of data data of fluctuations in the supply of oilseeds and oil reveals the effect of Ukrainian crisis on German food security as well. Official papers and statistic data analysis shows that Germany achieved self-sufficiency in basic food. The country focuses on strengthening the sustainability of agriculture and improving food quality in its national strategic papers. The weak element of food security is imports of oil and oilseeds, the supply of which declined in 2022. At the same time, raising prices and declining supplies of gas and fertilisers can become a serious threat to food security.